Exploring Chaplaincy Encounters with Particular Attention to the Non-Religious Patient: A Systematic Approach to Capturing the Content and Outcome of Conversations. (23rd May 2018) - Fraser, Derek; Ford, Debbie; Hunt, Susannah
Abstract : Hospital chaplaincy seeks to support the spiritual well-being of all those in hospital - whatever their worldviews of belief systems and however these are expressed. This study sought to explore of the current model of chaplaincy in addressing the spiritual needs of non-religious patients by developing a tool, called The Conversational Content Tool (CCT), which sought to understand those encounters in both a qualitative and quantitative manner. All weekday chaplain-patient encounters across all wards in Addenbrookes Hospital, Cambridge, 1 2 were categorized according to assessment of the patient's belief system - whether religious, non-religious or not known. After every encounter where the patient's belief system was identified as non-religious or not known, the chaplain completed a simple spread sheet (CCT) in order to describe the content and simple outcome measures of the encounter. Over 6 weeks, 1042 encounters were studied and categorized. The conversational content of 237 of the "non-religious/belief unstated" encounters was captured using the conversational content tool (CCT), yielding evidence of considerable identification of spiritual distress symptoms. The new research tool used for recording of encounters allowed expression of results in numerical and graphical form providing the potential for further development of work on chaplain-patient encounter.